An interface polarization dominated anisotropic effective medium wave-absorbing film and a preparation method thereof
Patent Information
- Application Number
- CN202611462531.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
究其原因,现有的异质结构的构建方法仍局限于组分的简单复合或特定形貌的复刻,难以对微观导电网络进行主动操纵
[0031](1)本发明的一种界面极化主导的各向异性等效介质吸波薄膜的制备方法,利用重力驱动的双相界面扩散聚合技术,一步高通量生成从轻度包覆到重度包覆、电导率从绝缘到高导电的全谱系核-壳纤维库,实现了对导电组分电导率分布的连续调控;方法操作简单,可在薄膜内构建电导率从绝缘到高导电连续分布的多分散导电网络。
Smart Images

Figure CN122978702A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic wave absorbing materials, and relates to an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization and its preparation method. Background Technology
[0002] With the rapid development of wireless communication, radar systems, and electronic countermeasures technologies, the propagation density of electromagnetic waves in modern information society is constantly increasing. How to effectively control the transmission, reflection, and dissipation of electromagnetic energy in materials has become a core research topic in electromagnetic functional materials. Among numerous strategies, microwave absorbing materials have attracted widespread attention because they can convert incident electromagnetic waves into heat energy. However, efficient absorption depends not only on the material's loss capacity but also on the degree of impedance matching between it and free space. In other words, various dielectric or magnetic loss mechanisms can only function when electromagnetic waves can smoothly enter the material's interior. Therefore, how to enhance electromagnetic loss while maintaining reasonable impedance matching remains a core scientific problem in the design of microwave absorbing materials.
[0003] Recent studies have shown that constructing microscopic heterostructures is considered an effective strategy for reshaping dielectric behavior and breaking the aforementioned physical impasse, with its core value lying in the introduction of complex microscopic physical mechanisms. Compared to homogeneous networks, heterostructure engineering can create regions with significantly different conductivity within the material, thereby introducing local barriers in the macroscopic conductive network and maintaining the overall conductivity near the percolation threshold, which is beneficial for achieving better impedance matching. Simultaneously, the abundant interfaces between different phases can induce carrier accumulation and relaxation at the interfaces, generating a significant Maxwell-Wagner polarization effect by constructing a microscale built-in electric field. Furthermore, the complex interface structure can also act as a scattering center, extending the propagation path of electromagnetic waves within the material and inducing multiple scattering and reflection processes, thereby further enhancing the electromagnetic wave attenuation capability. Therefore, constructing heterostructures with non-uniform conductivity distribution and abundant interface structures is considered an important approach to achieving broadband and efficient absorption.
[0004] Based on this consensus, researchers have extensively explored methods such as constructing core-shell structures and lattice doping to introduce rich interfaces to improve relaxation loss performance. Reference 1 (Bacterial cellulose nanofibers-assisted construction of core-shell structured polyaniline aerogel for superior electromagnetic wave absorption[J]. Carbohydrate Polymers, 2025, 352: 123239) describes the in-situ oxidative polymerization growth of polyaniline on the surface of bacterial nanocellulose to prepare conductive fibers with a core-shell heterostructure. Subsequently, a ternary composite aerogel absorbing material was prepared using a freeze-drying process, achieving a minimum reflection loss of -53.19 dB and a maximum effective absorption bandwidth of 2.20 GHz. Reference 2 (Rational design of hollow bimetallicsulfide@carbon with abundant heterogeneous interfaces and conductive networksynergies for efficient microwave absorption[J]. Carbon, 2024, 224: 119099) significantly enhanced the microwave attenuation performance of the material by utilizing the residual functional groups and lattice defects induced by sulfur doping, achieving a minimum reflection loss of -68.1 dB. While the above work achieved superior results in minimizing reflection loss, its effective absorption bandwidth is often narrow, and its performance is highly dependent on specific compositions and morphologies. The reason for this is that existing methods for constructing heterostructures are still limited to simple compositional composites or replication of specific morphologies, making it difficult to actively manipulate the microscopic conductive network. At the same time, even small fluctuations in the conductive component content near the percolation threshold can cause drastic changes in conductivity and impedance matching, making it difficult to stably control the microwave absorption performance. This limitation in manufacturing and control capabilities often makes it difficult to accurately translate the optimal electromagnetic parameter range locked by theoretical simulations into actual material structures, thus restricting the development of broadband, thin and lightweight microwave absorbing materials.
[0005] Therefore, it is of great significance to study an anisotropic equivalent dielectric absorbing film dominated by interface polarization and its preparation method to solve the problems existing in the prior art. Summary of the Invention
[0006] The purpose of this invention is to solve the problems existing in the prior art and to provide an anisotropic equivalent dielectric absorbing film dominated by interface polarization and its preparation method.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] An anisotropic equivalent dielectric absorbing film dominated by interface polarization is composed of a network of interwoven core-shell nanofibers. The core-shell nanofibers are formed by in-situ polymerization of aramid nanofibers (ANF) as the core layer and a conductive polymer shell coating on the surface.
[0009] The shell thicknesses of the core-shell nanofibers are not entirely uniform, resulting in a polydisperse distribution of electrical conductivity ranging from weak to high conductivity in the absorbing film. Adjacent core-shell nanofibers with varying conductivity form heterogeneous interfaces at their contact points, providing a site for carrier accumulation and relaxation, thereby enhancing interfacial polarization. Therefore, the absorbing film exhibits electrical heterogeneity with non-uniform conductivity distribution at the microscale.
[0010] In this invention, the fibers have different electrical conductivities due to their varying shell thicknesses. When two fibers with different conductivities overlap, the conductivity on both sides of the contact point is discontinuous, a phenomenon known as conductivity mismatch (analogous to connecting two wires with different resistances). Under an alternating electromagnetic field, charge carriers migrate easily on the side with higher conductivity but are hindered on the side with lower conductivity, thus accumulating at the contact interface and forming space charge polarization, i.e., interface polarization.
[0011] The composition of core-shell nanofibers (the types and proportions of core-shell nanofibers with different electrical conductivities in each region) within any macroscopic region (a region with a scale much larger than the diameter of a single fiber and containing a sufficient number of fibers to be statistically significant) and electromagnetic parameters are statistically consistent, meaning the film exhibits macroscopic statistical homogeneity in both composition and electromagnetic parameters. Furthermore, all core-shell nanofibers are preferentially oriented along the film surface to form a dense, wrinkled, layered structure, resulting in macroscopic anisotropy in the structural orientation of the absorbing film. It should be noted that "statistical homogeneity" here refers to the spatial distribution of composition and electromagnetic parameters, while "anisotropy" refers to structural orientation; these describe different physical properties and are not contradictory.
[0012] As a preferred technical solution:
[0013] The anisotropic equivalent dielectric absorbing film dominated by interface polarization as described above uses polypyrrole, polyaniline, or polythiophene as the conductive polymer.
[0014] As described above, an anisotropic equivalent dielectric absorbing film dominated by interface polarization has core-shell structured nanofibers of different shell thicknesses randomly distributed within the film.
[0015] As described above, the anisotropic equivalent dielectric absorbing film dominated by interface polarization has a maximum effective absorption bandwidth of 3.8 to 6.0 GHz in the 2 to 18 GHz (radar band) when the thickness is 1.2 to 2.1 mm; the minimum reflection loss of the absorbing film is -52.9 to -26.06 dB.
[0016] The present invention also provides a method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization as described above, comprising the following steps:
[0017] (1) Add an oxidant to the aqueous dispersion of aramid nanofibers, stir evenly, and then refrigerate at 0~6℃ to obtain an aqueous reaction solution;
[0018] (2) Dissolve the conductive polymer monomer in the oil phase reagent and stir until homogeneous to obtain the oil phase reaction solution;
[0019] (3) In a low temperature environment of 0~6℃, the oil phase reaction liquid obtained in step (2) is poured on top of the water phase reaction liquid obtained in step (1). No stirring is done during the addition process. The oil phase is spread smoothly on the water phase by taking advantage of the water-oil immiscibility to form a stable layered system with oil on top and water below.
[0020] (4) Maintain the low temperature environment of step (3) so that the conductive polymer monomers diffuse across the water-oil interface into the aqueous phase and undergo in-situ polymerization under the drive of gravity and concentration gradient, forming a system containing polydisperse core-shell structured nanofibers.
[0021] (5) After the reaction in step (4) is completed, the upper oil phase is removed and the lower aqueous phase system containing polydisperse core-shell structured nanofibers is repeatedly washed. Then, the system is homogenized and dispersed using a homogenizer to randomize the fibers that were originally distributed along the depth gradient of the aqueous phase. Subsequently, the core-shell structured nanofibers are preferentially oriented along the film surface under the action of solvent directional flow and layer-by-layer deposition to form a layered structure. Finally, the layered structure is densified by hot pressing to obtain an anisotropic equivalent dielectric absorbing film dominated by interface polarization.
[0022] As a preferred technical solution:
[0023] The preparation method of an anisotropic equivalent dielectric absorbing film dominated by interface polarization as described above, in step (1), the oxidant is ammonium persulfate or ferric chloride hexahydrate, and the concentration of the aqueous dispersion of aramid nanofibers is 3~10 mg / mL.
[0024] As described above, in the preparation method of an anisotropic equivalent dielectric absorbing film dominated by interface polarization, the oil phase reagent in step (2) is n-hexane or cyclohexane, and the conductive polymer monomer is pyrrole, aniline or thiophene. The oil phase reagent is an inert solvent, which is only used to dissolve the conductive polymer monomer and form an immiscible upper layer with the aqueous phase (to achieve stratification and serve as a reservoir for monomer diffusion to the interface). It does not participate in the polymerization reaction, so its amount is not a key parameter that determines the reaction. It is only necessary to dissolve the monomer and form an independent oil phase layer above the aqueous phase. The mass ratio of conductive polymer monomer to aramid nanofiber is 6~10:25, and the molar ratio of conductive polymer monomer to oxidant is 1:0.8~1.2.
[0025] In the preparation method of an anisotropic equivalent dielectric absorbing film dominated by interface polarization as described above, the volume ratio of oil phase reaction liquid to water phase reaction liquid in step (3) is 2~3:5.
[0026] In the preparation method of an anisotropic equivalent dielectric absorbing film dominated by interface polarization as described above, the reaction time in step (4) is 4 to 6 hours.
[0027] In the preparation method of an anisotropic equivalent dielectric absorbing film dominated by interface polarization as described above, the hot pressing temperature in step (5) is 80~120℃.
[0028] Invention principle:
[0029] The microwave absorbing film of this invention is prepared in a two-phase system consisting of an oil phase and an aqueous phase. In this system, the lower layer is an aqueous solution containing an oxidant, and the upper layer is an oil phase solution containing conductive polymer monomers. During the in-situ polymerization reaction, the conductive polymer monomers slowly diffuse across the liquid-liquid interface into the aqueous phase under the drive of gravity and concentration difference, establishing a continuous monomer concentration gradient from top to bottom in the aqueous phase. This causes the thickness of the conductive polymer shell coating on the surface of the aramid nanofibers to continuously vary along the depth, spontaneously generating a full-spectrum core-shell fiber library ranging from light to heavy coating and from weak to high conductivity. Subsequently, the washed fiber product undergoes homogenization dispersion treatment, randomizing the fibers distributed along the depth gradient. In a typical reaction system, the reaction proceeds uniformly, resulting in a film with various fibers interwoven at the microscopic level, all with the same fiber diameter, thus exhibiting microscopic homogeneity and macroscopic homogeneity. In the reaction system of this invention, a water-oil interface is constructed, and the reaction occurs in the aqueous phase. However, because the concentration of conductive polymer monomers in contact with different aqueous phase heights is different, the core-shell fibers obtained after the reaction have different diameters and different conductivity properties. This invention does not retain this gradient structure; instead, it utilizes a homogeneous dispersion step to completely disrupt the fiber distribution that varies with height, allowing fibers of various diameters to be randomly distributed in the solution. After vacuum filtration and hot-pressing densification, the fibers are oriented along the membrane surface under the action of flow field and pressure, assembling into a dense, wrinkled, layered structure. In this structure, the high-conductivity component (thick shell) constructs long-range electron transport paths, providing the basic conduction loss; the low-conductivity component (thin shell or exposed ANF) acts as a dielectric isolation framework, effectively diluting the connectivity density of the conductive network and preventing premature impedance collapse; adjacent fibers with mismatched conductivity form a large number of heterogeneous micro-interfaces at the contact points, establishing a loss mechanism dominated by interfacial polarization. Because the fiber conductivity exhibits a polydisperse continuous distribution, the percolation transition of the system changes from abrupt to gradual, exhibiting tunable soft percolation equivalent medium behavior: changes in the content of conductive components no longer cause drastic jumps in conductivity and impedance matching, but rather a gradual transition, thus forming a wider adjustable window between impedance matching and electromagnetic attenuation; combined with the strong interfacial polarization (relaxation loss) brought about by a large number of heterogeneous interfaces, the film can enhance the attenuation of incident electromagnetic waves while maintaining good impedance matching, thereby broadening the effective absorption bandwidth of the radar band.
[0030] Beneficial effects:
[0031] (1) The present invention provides a method for preparing anisotropic equivalent dielectric absorbing thin film dominated by interface polarization. It utilizes gravity-driven two-phase interface diffusion polymerization technology to generate a full spectrum of core-shell fiber libraries ranging from light coating to heavy coating and conductivity from insulating to highly conductive in one step with high throughput, thereby realizing continuous control of the conductivity distribution of conductive components. The method is simple to operate and can construct a multi-dispersed conductive network with a continuous conductivity distribution from insulating to highly conductive within the thin film.
[0032] (2) The present invention provides a method for preparing an anisotropic equivalent dielectric absorbing film dominated by interface polarization. By homogenizing the reaction products, the conductivity gradient formed along the depth during the preparation process is broken up. The disordered fibers are assembled into a dense folded layered structure with in-plane orientation in vacuum filtration and hot pressing. A heterogeneous interface with massive conductivity mismatch is formed at the fiber-fiber contact, thus establishing a loss mechanism dominated by interface polarization.
[0033] (3) The present invention provides a method for preparing an anisotropic equivalent dielectric absorbing film dominated by interface polarization, which expands the construction method of heterostructure of absorbing material, enhances interface polarization (relaxation loss), and improves the attenuation capability and effective absorption bandwidth of radar waves while ensuring impedance matching.
[0034] (4) An interface polarization-dominated anisotropic equivalent dielectric absorbing film of the present invention contains both high conductivity fibers that bear conduction loss and low conductivity fibers that act as dielectric skeleton and optimize impedance matching. The various fibers are randomly distributed, so that the film exhibits tunable soft percolation equivalent dielectric behavior and has a wider adjustable window between impedance matching and electromagnetic attenuation.
[0035] (5) The present invention provides an anisotropic equivalent dielectric absorbing film dominated by interface polarization. By utilizing its soft percolation characteristics, the change in the content of conductive components will not cause a drastic change in conductivity, thereby achieving a balance between impedance matching and electromagnetic attenuation. Furthermore, by introducing a large number of heterogeneous interfaces with mismatched conductivity, the interface polarization (relaxation loss) is enhanced, thereby broadening the effective absorption bandwidth of the absorbing film in the radar band. Attached Figure Description
[0036] Figure 1 The preparation process of anisotropic equivalent dielectric absorbing thin films dominated by interface polarization (including diffusion polymerization process at the water-oil interface).
[0037] Figure 2 For Example 1, during the preparation of a high-throughput core-shell fiber library using a gravity-driven interfacial polymerization strategy, a series of optical photographs were taken to record the reaction at each stage over time.
[0038] Figure 3 The images show the microstructure of the anisotropic equivalent dielectric absorbing film dominated by interface polarization in Example 1 at different sizes; (a) is a surface image at 400 nm; (b) is a cross-sectional image at 400 nm; and (c) is a TEM image at 200 nm.
[0039] Figure 4The following is a graph showing the reflection loss data of the anisotropic equivalent dielectric absorbing film dominated by interface polarization in Example 1; (a) is the dielectric constant data of the absorbing film; (b) is the overall absorption performance of the absorbing film in the 2~18GHz frequency band and the thickness range of 0.1~4mm; (c) is a dotted line graph of the reflection loss of the absorbing film.
[0040] Figure 5 The images show the microstructure of the anisotropic equivalent dielectric absorbing film dominated by interface polarization in Comparative Example 1 at different sizes; (a) is the SEM surface image at 400 nm; (b) is the SEM cross-sectional image at 400 nm; and (c) is the TEM image at 200 nm.
[0041] Figure 6 The following is a graph showing the reflection loss data of the anisotropic equivalent dielectric absorbing film dominated by interface polarization in Comparative Example 1; (a) shows the dielectric constant data of the absorbing film; (b) shows the overall absorption performance of the absorbing film in the 2~18GHz frequency band and the thickness range of 0.1~4mm; (c) shows the reflection loss of the absorbing film.
[0042] Figure 7 The following is a graph showing the reflection loss data of the anisotropic equivalent dielectric absorbing film dominated by interface polarization in Example 2; (a) is the dielectric constant data of the absorbing film; (b) is the overall absorption performance of the absorbing film in the 2~18GHz frequency band and the thickness range of 0.1~4mm; (c) is a dotted line graph of the reflection loss of the absorbing film.
[0043] Figure 8 The following is a graph showing the reflection loss data of the anisotropic equivalent dielectric absorbing film dominated by interface polarization in Example 3; (a) is the dielectric constant data of the absorbing film; (b) is the overall absorption performance of the absorbing film in the 2~18GHz frequency band and the thickness range of 0.1~4mm; (c) is a dotted line graph of the reflection loss of the absorbing film. Detailed Implementation
[0044] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0045] The test methods involved in the performance indicators in the embodiments and comparative examples of this invention are as follows:
[0046] The absorption performance (reflection loss, effective absorption bandwidth) of the absorbing film in the radar band is determined by its electromagnetic parameters (complex permeability μ). r Complex permittivity ε rThe electromagnetic parameters were calculated using a Keysight E5080B vector network analyzer, in accordance with GB / T 35679-2017, with a frequency range of 2~18GHz. The test sample was made into a concentric ring with an inner diameter of 3.04mm and an outer diameter of 7.00mm. The test was conducted using the coaxial testing method on the Keysight E5080B vector network analyzer, and the electromagnetic parameters were obtained using the accompanying N1500A software.
[0047] The formula for calculating reflection loss RL (dB) is as follows:
[0048] ;
[0049] ;
[0050] In the formula, Input impedance (Ω). The impedance of air is 377 Ω. To obtain the complex permittivity by testing, To obtain the complex permeability by testing, The thickness (mm) of the absorbing film. and These are frequency (GHz) and the speed of light in a vacuum (3 × 10⁻⁶), respectively. 8 (m / s). In this invention, the frequency range corresponding to a reflection loss RL ≤ -10 dB (corresponding to an incident electromagnetic wave absorption rate ≥ 90%) is defined as the effective absorption bandwidth.
[0051] The preparation process of the aramid nanofiber aqueous dispersion used in the following embodiments is as follows:
[0052] Short-cut Kevlar fibers (manufacturer: DuPont, brand name 1414), potassium hydroxide, dimethyl sulfoxide, and deionized water were mixed at a mass ratio of Kevlar fibers: potassium hydroxide: dimethyl sulfoxide = 1:1.5:100 and stirred at 50°C and 500 rpm for 24 h. Then, deionized water (the mass ratio of dimethyl sulfoxide to the added deionized water was 1:25) was added, and stirring was continued for 2 h. The resulting dispersion was then washed by repeatedly injecting deionized water and filtering. After washing, colloidal dispersions of 3 mg / mL, 5 mg / mL, and 10 mg / mL were quantitatively prepared and homogenized at 10000 rpm for 20 min using a homogenizer to obtain aqueous dispersions of aramid nanofibers of different concentrations for later use.
[0053] Example 1
[0054] A method for preparing anisotropic equivalent dielectric absorbing thin films dominated by interface polarization, such as... Figure 1 As shown, the specific steps are as follows:
[0055] (1) Preparation of raw materials;
[0056] Aramid nanofiber aqueous dispersion: 5 mg / mL;
[0057] Ammonium persulfate: CAS number 7727-54-0;
[0058] Pyrrole monomer: CAS number 109-97-7;
[0059] Cyclohexane: CAS number 110-82-7;
[0060] (2) Add ammonium persulfate to the aqueous dispersion of aramid nanofibers, stir evenly under an ice-water bath, and then refrigerate at 0°C to obtain an aqueous reaction solution;
[0061] (3) Dissolve the pyrrole monomer in cyclohexane and stir until homogeneous to obtain an oil phase reaction solution;
[0062] The mass ratio of pyrrole monomer to aramid nanofibers is 8:25; the molar ratio of pyrrole monomer to ammonium persulfate is 1:0.8.
[0063] (4) At a low temperature of 0℃, the oil phase reaction liquid obtained in step (3) is poured onto the water phase reaction liquid obtained in step (2) to form a stable layered system with oil on top and water below.
[0064] The volume ratio of the oil phase reaction liquid to the aqueous phase reaction liquid is 2:5.
[0065] (5) Maintain the low temperature environment of step (4) so that the pyrrole monomer diffuses across the water-oil interface into the aqueous phase under the drive of gravity and concentration gradient and undergoes in-situ polymerization reaction for 4 hours to form a system containing polydisperse core-shell structured nanofibers.
[0066] like Figure 2 As shown, initially, only a small amount of black (conductive polymer: polypyrrole) was visible in the upper layer of the aqueous phase. As time progressed, the black area in the lower aqueous phase increased, demonstrating that the polymerization reaction was gradually induced from top to bottom.
[0067] Figure 1 and Figure 2 This demonstrates the successful construction of the liquid-liquid interface and the sequential color changes of the subsequent lower solution, indicating that the in-situ polymerization of materials in the lower system is asynchronous and non-uniform, meaning the shell thickness varies. This provides a basis for the subsequent homogenization process, which revealed that the membrane is composed of interwoven fibers with different electrical conductivities.
[0068] (6) After the reaction in step (5) is completed, the upper oil phase is removed and the lower aqueous phase system containing polydisperse core-shell structured nanofibers is repeatedly washed; then the system is homogenized and dispersed using a homogenizer; then it is vacuum filtered to form a layered structure; finally, the layered structure is densified by hot pressing at 120℃ to obtain an anisotropic equivalent dielectric absorbing film dominated by interface polarization.
[0069] The final anisotropic equivalent dielectric absorbing film dominated by interface polarization is composed of a network of interwoven core-shell nanofibers. These core-shell nanofibers are formed with aramid nanofibers as the core layer and a polypyrrole shell layer formed by in-situ polymerization. The shell thicknesses of the core-shell nanofibers are not entirely uniform, resulting in a polydisperse distribution of conductivity from weak to high within the absorbing film. Adjacent core-shell nanofibers with different conductivityes form heterogeneous interfaces with conductivity mismatch at their contact points. The composition of the core-shell nanofibers in any macroscopic region within the absorbing film is statistically consistent with its electromagnetic parameters. Core-shell nanofibers of different shell thicknesses are randomly distributed within the film, and all core-shell nanofibers are preferentially oriented along the film surface, forming a layered structure, resulting in macroscopic anisotropy in the structural orientation of the absorbing film. Figure 3 As shown, the obtained absorbing film exhibits a morphology of randomly interwoven, in-plane oriented core-shell nanofibers with polydisperse conductivity; the anisotropic equivalent dielectric absorbing film dominated by interfacial polarization, with a thickness of 2.1 mm, has a maximum effective absorption bandwidth of 5.7 GHz (covering 11.5–17.2 GHz) within the range of 2–18 GHz; the minimum reflection loss of the entire absorbing film is -48.95 dB (e.g., ...). Figure 4 (As shown).
[0070] Comparative Example 1
[0071] A method for preparing an anisotropic equivalent dielectric absorbing film dominated by interface polarization is basically the same as in Example 1, except that: in step (5), the entire reaction system is kept under continuous stirring throughout the reaction process.
[0072] like Figure 5 As shown, Comparative Example 1 does not have the process of slowly passing down the polymer. The pyrrole monomer is uniformly distributed in the aqueous phase and undergoes in-situ polymerization directly. The fibers after the reaction are intertwined.
[0073] With a thickness of 1.1 mm, the resulting film has a maximum effective absorption bandwidth of 3.3 GHz in the 2–18 GHz range (covering 14.7–18.0 GHz); the minimum reflection loss of the entire absorbing film is -15.90 dB (e.g., Figure 6 (As shown).
[0074] Compared with Example 1, under the same reaction conditions and component concentrations, Comparative Example 1 changed the polymerization, which was originally controlled by gradual diffusion at the water-oil interface, to continuous and uniform polymerization in the aqueous phase. The effective absorption bandwidth and minimum reflection loss of the resulting film were significantly worse. The reason is that continuous stirring makes the monomer concentration in contact with each fiber surface tend to be uniform, the thickness of the conductive polymer shell is uniform, the fiber conductivity is monodisperse, and the heterogeneous interface with conductivity mismatch is no longer formed. The interface polarization (relaxation loss) and the adjustable soft percolation characteristics are weakened, resulting in a decrease in the film's attenuation ability to electromagnetic waves and the effective absorption bandwidth.
[0075] Example 2
[0076] A method for preparing an anisotropic equivalent dielectric absorbing film dominated by interface polarization is basically the same as in Example 1, except that the mass ratio of pyrrole monomer to aramid nanofiber in step (3) is 6:25.
[0077] The finally fabricated anisotropic equivalent dielectric absorbing film dominated by interface polarization, with a thickness of 2.1 mm, has a maximum effective absorption bandwidth of 5.1 GHz in the range of 2–18 GHz (covering 12.3–17.4 GHz); the minimum reflection loss of the entire absorbing film is -47.11 dB (e.g., ...). Figure 7 (As shown).
[0078] Comparing Example 2 with Example 1, it can be seen that Example 2 reduced the mass ratio of pyrrole monomer to aramid nanofibers. The reduced content of conductive components decreased the overall conductivity of the film and improved impedance matching, but the attenuation capability of the conductive network was correspondingly weakened. Considering both factors, the effective absorption bandwidth and minimum reflection loss of Example 2 were slightly lower than those of Example 1. This indicates that there is an optimal range for the content of conductive components in this system, and it can be controlled within a wide window using soft percolation characteristics to approach the optimum.
[0079] Example 3
[0080] A method for preparing an anisotropic equivalent dielectric absorbing film dominated by interface polarization is basically the same as in Example 1, except that the molar ratio of pyrrole monomer to ammonium persulfate in step (3) is 1:1.
[0081] The finally fabricated anisotropic equivalent dielectric absorbing film dominated by interface polarization, with a thickness of 1.9 mm, has a maximum effective absorption bandwidth of 5.7 GHz in the range of 2–18 GHz (covering 11.7–17.4 GHz); the minimum reflection loss of the entire absorbing film is -26.06 dB (e.g., ...). Figure 8 (As shown).
[0082] Example 4
[0083] A method for preparing an anisotropic equivalent dielectric absorbing film dominated by interface polarization is basically the same as in Example 1, except that: in step (3), the mass ratio of pyrrole monomer to aramid nanofiber is 6:25; and the molar ratio of pyrrole monomer to ammonium persulfate is 1:1.2.
[0084] The final fabricated anisotropic equivalent dielectric absorbing film dominated by interface polarization has a maximum effective absorption bandwidth of 6.0 GHz in the range of 2 to 18 GHz (covering 11.7 to 17.7 GHz) with a thickness of 2.0 mm; the minimum reflection loss of the entire absorbing film is -52.90 dB.
[0085] Example 5
[0086] A method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization, comprising the following specific steps:
[0087] (1) Preparation of raw materials;
[0088] Aramid nanofiber aqueous dispersion: 10 mg / mL;
[0089] Ferric chloride hexahydrate: CAS number 10025-77-1;
[0090] Aniline monomer: CAS number 62-53-3;
[0091] n-Hexane: CAS number 110-54-3;
[0092] (2) Add ferric chloride hexahydrate to the aqueous dispersion of aramid nanofibers, stir evenly under an ice-water bath, and then refrigerate at 0°C to obtain an aqueous reaction solution;
[0093] (3) Dissolve the aniline monomer in n-hexane and stir evenly under an ice-water bath to obtain an oil phase reaction solution;
[0094] The mass ratio of aniline monomer to aramid nanofiber is 8:25; the molar ratio of aniline monomer to ferric chloride hexahydrate is 1:1.
[0095] (4) At a low temperature of 0℃, the oil phase reaction liquid obtained in step (3) is poured onto the water phase reaction liquid obtained in step (2) to form a stable layered system with oil on top and water below.
[0096] The volume ratio of the oil phase reaction liquid to the aqueous phase reaction liquid is 3:5.
[0097] (5) Maintain the low temperature environment of step (4) so that the aniline monomer diffuses across the water-oil interface into the aqueous phase under the drive of gravity and concentration gradient and undergoes in-situ polymerization reaction for 4 hours to form a system containing polydisperse core-shell structured nanofibers.
[0098] (6) After the reaction in step (5) is completed, the upper oil phase is removed and the lower aqueous phase system containing polydisperse core-shell structured nanofibers is repeatedly washed; then the system is homogenized and dispersed using a homogenizer; then it is vacuum filtered to form a layered structure; finally, the layered structure is densified by hot pressing at 120℃ to obtain an anisotropic equivalent dielectric absorbing film dominated by interface polarization.
[0099] The final anisotropic equivalent dielectric absorbing film dominated by interface polarization is composed of a network of interwoven core-shell nanofibers. These core-shell nanofibers are formed by in-situ polymerization of aramid nanofibers as the core layer and a polyaniline shell. The shell thicknesses of the individual core-shell nanofibers are not entirely uniform, resulting in a polydisperse distribution of conductivity ranging from weak to high within the absorbing film. Adjacent core-shell nanofibers with different conductivityes form heterogeneous interfaces with conductivity mismatch at their contact points. Within any macroscopic region of the absorbing film… The composition and electromagnetic parameters of the core-shell nanofibers in the region are statistically consistent; each core-shell nanofiber is randomly distributed within the film, and all core-shell nanofibers are preferentially oriented along the film surface to form a layered structure, making the absorbing film macroscopically anisotropic in structural orientation; the anisotropic equivalent dielectric absorbing film dominated by interface polarization has a maximum effective absorption bandwidth of 3.8 GHz (covering 12.6~16.4 GHz) in the range of 2~18 GHz when the thickness is 1.6 mm; the minimum reflection loss of the entire absorbing film is -43.54 dB.
[0100] Example 6
[0101] A method for preparing an anisotropic equivalent dielectric absorbing film dominated by interface polarization is basically the same as in Example 5, except that: in step (3), the mass ratio of aniline monomer to aramid nanofiber is 6:25; and the molar ratio of aniline monomer to ammonium persulfate is 1:1.2.
[0102] The final fabricated anisotropic equivalent dielectric absorbing film dominated by interface polarization has a maximum effective absorption bandwidth of 4.1 GHz (covering 13.5~17.6 GHz) in the range of 2~18 GHz with a thickness of 1.5 mm; the minimum reflection loss of the entire absorbing film is -44.77 dB.
[0103] Example 7
[0104] A method for preparing an anisotropic equivalent dielectric absorbing film dominated by interface polarization is basically the same as in Example 5, except that the refrigeration temperature in steps (2) and (4) is 4°C and the reaction time in step (5) is 6h.
[0105] The final fabricated anisotropic equivalent dielectric absorbing film dominated by interface polarization has a maximum effective absorption bandwidth of 4.1 GHz (covering 12.4 to 16.5 GHz) in the range of 2 to 18 GHz with a thickness of 1.2 mm; the minimum reflection loss of the entire absorbing film is -28.91 dB.
[0106] Example 8
[0107] A method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization, comprising the following specific steps:
[0108] (1) Preparation of raw materials;
[0109] Aramid nanofiber aqueous dispersion: 3 mg / mL;
[0110] Ferric chloride hexahydrate: CAS number 10025-77-1;
[0111] Thiophene monomer: CAS number 110-02-1;
[0112] Cyclohexane: CAS number 110-82-7;
[0113] (2) Add ferric chloride hexahydrate to the aqueous dispersion of aramid nanofibers, stir evenly under an ice-water bath, and then refrigerate at 0°C to obtain an aqueous reaction solution;
[0114] (3) Dissolve the thiophene monomer in cyclohexane and stir evenly under an ice-water bath to obtain an oil phase reaction solution;
[0115] The mass ratio of thiophene monomer to aramid nanofiber is 8:25; the molar ratio of thiophene monomer to ferric chloride hexahydrate is 1:1.
[0116] (4) At a low temperature of 0℃, the oil phase reaction liquid obtained in step (3) is poured onto the water phase reaction liquid obtained in step (2) to form a stable layered system with oil on top and water below.
[0117] The volume ratio of the oil phase reaction liquid to the aqueous phase reaction liquid is 2:5.
[0118] (5) Maintain the low temperature environment of step (4) so that the thiophene monomer diffuses across the water-oil interface into the aqueous phase under the drive of gravity and concentration gradient and undergoes in-situ polymerization reaction for 4 hours to form a system containing polydisperse core-shell structured nanofibers.
[0119] (6) After the reaction in step (5) is completed, the upper oil phase is removed and the lower aqueous phase system containing polydisperse core-shell structured nanofibers is repeatedly washed; then the system is homogenized and dispersed using a homogenizer; then it is vacuum filtered to form a layered structure; finally, the layered structure is densified by hot pressing at 100℃ to obtain an anisotropic equivalent dielectric absorbing film dominated by interface polarization.
[0120] The final anisotropic equivalent dielectric absorbing film dominated by interface polarization is composed of a network of interwoven core-shell nanofibers. These core-shell nanofibers are formed with aramid nanofibers as the core layer and a polythiophene shell layer formed by in-situ polymerization. The shell thicknesses of the core-shell nanofibers are not entirely uniform, resulting in a polydisperse distribution of conductivity from weak to high within the absorbing film. Adjacent core-shell nanofibers with different conductivity form heterogeneous interfaces with conductivity mismatch at their contact points. Within any macroscopic region of the absorbing film… The composition and electromagnetic parameters of the core-shell nanofibers in the region are statistically consistent; each core-shell nanofiber is randomly distributed within the film, and all core-shell nanofibers are preferentially oriented along the film surface to form a layered structure, making the absorbing film macroscopically anisotropic in structural orientation; the anisotropic equivalent dielectric absorbing film dominated by interface polarization has a maximum effective absorption bandwidth of 4.6 GHz (covering 12.7~17.3 GHz) in the range of 2~18 GHz when the thickness is 1.5 mm; the minimum reflection loss of the entire absorbing film is -43.87 dB.
Claims
1. An anisotropic equivalent dielectric absorbing thin film dominated by interface polarization, characterized in that: It is composed of a network of interwoven core-shell nanofibers, which are formed by in-situ polymerization of aramid nanofibers as the core layer and a conductive polymer shell coating on the surface. The shell thickness of each core-shell nanofiber is not exactly the same, which makes the conductivity of the core-shell nanofiber in the microwave absorbing film exhibit a polydisperse distribution from weak conductivity to high conductivity; adjacent core-shell nanofibers with different conductivity form a heterogeneous interface with conductivity mismatch at the contact point. The composition and electromagnetic parameters of the core-shell nanofibers in any macroscopic region within the absorbing film are statistically consistent; and all core-shell nanofibers are preferentially oriented along the film surface and form a layered structure, making the absorbing film macroscopically anisotropic in structural orientation.
2. The anisotropic equivalent dielectric absorbing thin film dominated by interface polarization according to claim 1, characterized in that, The conductive polymer is polypyrrole, polyaniline, or polythiophene.
3. The anisotropic equivalent dielectric absorbing thin film dominated by interface polarization according to claim 2, characterized in that, Core-shell nanofibers with different shell thicknesses are randomly distributed within the membrane.
4. The anisotropic equivalent dielectric absorbing thin film dominated by interface polarization according to claim 3, characterized in that, The anisotropic equivalent dielectric absorbing film dominated by interface polarization has a maximum effective absorption bandwidth of 3.8 to 6.0 GHz in the range of 2 to 18 GHz when the thickness is 1.2 to 2.1 mm. The minimum reflection loss of the anisotropic equivalent dielectric absorbing film dominated by interface polarization is -52.9 to -26.06 dB.
5. A method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization as described in any one of claims 1 to 4, characterized in that... Includes the following steps: (1) Add an oxidant to the aqueous dispersion of aramid nanofibers, stir evenly, and then refrigerate at 0~6℃ to obtain an aqueous reaction solution; (2) Dissolve the conductive polymer monomer in the oil phase reagent and stir until homogeneous to obtain the oil phase reaction solution; (3) In a low temperature environment of 0~6℃, the oil phase reaction liquid obtained in step (2) is poured on top of the aqueous phase reaction liquid obtained in step (1) to form a stable layered system with oil on top and water below. (4) Maintain the low temperature environment of step (3) so that the conductive polymer monomers diffuse across the water-oil interface into the aqueous phase and undergo in-situ polymerization under the drive of gravity and concentration gradient, forming a system containing polydisperse core-shell structured nanofibers. (5) After the reaction in step (4) is completed, the upper oil phase is removed and the lower aqueous phase system containing polydisperse core-shell structured nanofibers is repeatedly washed; then the system is homogenized and dispersed using a homogenizer; then it is vacuum filtered to form a layered structure; finally, the layered structure is densified by hot pressing to obtain an anisotropic equivalent dielectric absorbing film dominated by interface polarization.
6. The method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization according to claim 5, characterized in that, In step (1), the oxidant is ammonium persulfate or ferric chloride hexahydrate, and the concentration of the aqueous dispersion of aramid nanofibers is 3~10 mg / mL.
7. The method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization according to claim 5, characterized in that, In step (2), the oil phase reagent is n-hexane or cyclohexane, and the conductive polymer monomer is pyrrole, aniline or thiophene; the mass ratio of the conductive polymer monomer to the aramid nanofiber is 6~10:25, and the molar ratio of the conductive polymer monomer to the oxidant is 1:0.8~1.
2.
8. The method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization according to claim 5, characterized in that, In step (3), the volume ratio of the oil phase reaction liquid to the water phase reaction liquid is 2~3:
5.
9. The method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization according to claim 5, characterized in that, The reaction time in step (4) is 4 to 6 hours.
10. The method for preparing an anisotropic equivalent dielectric absorbing thin film dominated by interface polarization according to claim 5, characterized in that, The hot pressing temperature in step (5) is 80~120℃.